Hunger and food security among older adults in a rural community - Quandt, Sara A.; Rao, Pamela (1999)
Although government policies over the last several decades have addressed issues of nutrition for the elderly, elders still face problems of undernutrition and food insecurity. This study assesses the level of food insecurity and identifies predictors among 192 residents 65 years and older in rural Appalachia. Participants were recruited using a site-based rapid recruitment technique, and data were collected using structured questionnaires in face-to-face interviews. Twenty-four percent report one or more food insecurity indicator. Health, social, and material barriers all predict food insecurity in bivariate analyses. In logistic regression, taking three or more prescription drugs, eating along, and income less than 150% of poverty level are the strongest predictors of food insecurity. The high rate of food insecurity and its predictors are examined in terms of policies aimed to reduce nutrition problems for elders, the life course experiences of elders, the economic history of the area, and more general problems in getting sufficient food faced by older rural adults. - Reproduced
Keywords: Nutrition; Hunger; Poverty; Food supply; Elderly